America for Americans : a history of xenophobia in the United States - Lee, Erika (Basic Books, 2019)
"Many of us like to think of the United States as a nation of immigrants. We pride ourselves on our history of welcoming foreigners and believe this sets our nation apart from every other. But the phrase 'a nation of immigrants' only dates from the mid-twentieth century, and has served to paper over a much darker history of hatred of -- and violence against -- foreigners arriving on our shores. As the acclaimed historian Erika Lee shows in America for Americans, the recent spasm of xenophobic policy and treatment of immigrants -- from the abuses of ICE to the Muslim ban to the proposed border wall -- is only the latest manifestation of another, less known but even more influential American creed. As Lee argues, an intense fear of strangers based on their race, religion, ethnicity, or national origin has always been at the heart of the American project. From Benjamin Franklin calling German immigrants 'swarthy' aliens to the anti-Chinese exclusion movement in 1876 San Francisco to modern paranoia over Mexican immigration and the 'browning of America,' xenophobia has been an ideological force working hand-in-hand with American nationalism, capitalism, and racism. Offering a new framework and theory of xenophobia to explain what it is, what it does, and how it works, Lee shows that more often than not in our nation's history, xenophobia has been the rule -- not the exception. At the same time, she reveals why we cannot understand institutionalized racism, sexism, classism without first examining the role of xenophobia in creating these related problems. Forcing us to reckon with the less palatable side of American history and beliefs, America for Americans is a necessary corrective and ultimately a spur to action for any concerned citizen"--